Linguistic strategies in attracting YouTube subscribers: A pragmatics perspective - Yanti, Dewi (Journal of Research on English and Language Learning (J-REaLL), 2025)
The rapid development of digital media has changed communication patterns, making YouTube a competitive space to attract and retain audiences. However, the study of creators' linguistic strategies in the context of digital marketing communication through speech act theory is still limited. This study aims to examine the linguistic strategies used by YouTube content creators to attract attention and increase the number of subscribers, using a pragmatic approach based on Searle speech act theory. The main focus of this study is to identify the types of speech acts such as assertives, directives, commissives, expressives, and declaratives that appear in various YouTube videos, as well as their strategic roles in building relationships with audiences. The research method used is descriptive qualitative with data collection techniques through observation and video transcription from seven relevant YouTube sources. The results of the study show that directive and assertive speech acts dominate the speech used by creators, especially in invitations to like, subscribe, and follow the links provided. Commissive and expressive speech acts also play an important role in creating emotional attachment and building trust. These findings indicate that linguistic strategies through speech acts are an effective tool in digital communication to influence audience behavior and expand the reach of content. These findings also expand the application of pragmatic theory in digital media and creative content, and contribute to the study of applied linguistics and media literacy. However, limited data, subjectivity of interpretation, and the lack of consideration of multimodal aspects indicate the need for further research with a broader scope and approach.